Novel true random bit generation and its audio encryption application with Lorenz chaotic circuit-based entropy source - İnce, Esra; Karakaya, Barış; Türk, Mustafa (My University, 2024)
This paper introduces a methodology for generating secure cryptographic key bits from analog values obtained from the Lorenz chaotic circuit. The analog values are transferred from the chaotic circuit to the computer via an Analog Discovery-2 device and then post-processed by using a fixed-point number representation format and Von-Neumann corrector for the sampled values on the MATLAB program. By employing this method, the analog values are digitized and randomized as the main idea is to obtain secure and efficient statistically random bits. Furthermore, the generated random bits are utilized for secure audio encryption by demonstrating a practical application of the proposed methodology. In addition to the classical randomness test criteria, NIST 800.22 statistical test suite, the throughput bit stream is also subjected to Chi-square and FIPS 140-1 tests to further evaluate its effectiveness. The results of these comprehensive tests confirm the successful performance of the proposed system in generating statistically random bits and its secure audio encryption system. The utilization of the Lorenz chaotic circuit as an entropy source in generating true random bits for secure audio transmission applications showcases the potential of the proposed system.
Keywords: Chaos; Random Number Generator; Audio Encryption; Post-processor; Statistical Tests